Process safety management in manufacturing industries a review - Silaipillayarputhur, Karthik (International Journal of Engineering and Technology, 2018)
The most common feature among the best known companies in the world is safety. In fact, process safety and manufacturing productivity go hand in hand. In the last century, a number of catastrophic accidents have drawn the attention of regulators towards process safety. In several developed, industrialized countries, strict regulations and standards are applied to emphasize process safety. In fact, in such countries, these are the required minimum for maintaining business license and permits. However, in developing and in under developed nations, the issue of process safety and their importance is still being debated. Process safety cannot just be driven by a set of rules, regulations, policies, etc. Multitudes of items are required in establishing and maintaining a safe and a reliable work environment. Such items, though can be expressed readily in paper, are quite arduous to establish in a highly competitive environment. The legislation, the government regulations, banking policies, management commitment, cumulatively share the responsibility in establishing organizations judiciously managing process safety. This paper reviews certain critical aspects in establishing a successful process safety management (PSM) program. Furthermore, the paper reviews the various elements that contribute towards the creation of a worthwhile PSM program.